The accountability of the Criminal Case Relating to the Act made by Act No. 2 of 2014 - Danar Setyo Wibowo; Alfian Faulia Numairi; Sri Endah Wahyuningsih (Jurnal Akta, 2019)
Notaries are public officials appointed by the government to help the public make the agreements which are or appear in public. The purpose of the presence of a written agreement is to ensure legal certainty of the stakeholders of the agreement. The written agreement made before a notary deed called. Atka could be used as evidence if there is a dispute between the parties to the dispute, with the explanation of the importance of this function in tulisakan act until the regulations of Law No. 2 of 2014Keywords: notary; Responsibility for crime; legal protection